Fault Delineation Using Magnetic Data in Eastern Part of Chiang Mai Basin, Thailand - Chawanun Ninsom (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
Fault is displacement of rocks along a shear surface and its location can be represented as a variation in a magnetic field. Fault location can provide information on earthquake hazard estimation and hydrothermal sources and related geological resources. The study area is located in the eastern part of the Chiang Mai basin that is covered by Quaternary and Tertiary sediment. The enhancement techniques were applied to both aeromagnetic data and ground magnetic data. The Euler deconvolution is a technique for estimating the depth and the location of magnetic sources. In applying Euler deconvolution, one must select an appropriate structure index. Windows sizes were employed to limit the number of grid calculation in the equation. A trial and error technique was used to determine the best number of structure index and window size. From the Euler interpretation map of aeromagnetic data, some N-S trending faults can be detected with depth of about 400 – 2,000 meters. The aeromagnetic data cannot detect shallow faults because of the limit of flight line interval resolution. Therefore three areas of ground magnetic survey have been conducted. From ground magnetic data, the interpretation map shows a near surface fault trending as same as possible fault line with depth of about 10 – 200 meters. This particular fault is located near the city area but has previously not been documented. The results from this study provide vital information for earthquake hazard mitigation and city planning.